Analysis of the Rice ADP-Glucose Transporter (OsBT1) Indicates the Presence of Regulatory Processes in the Amyloplast Stroma That Control ADP-Glucose Flux into Starch . Issue 3 (11th January 2016) - Cakir, Bilal; Shiraishi, Shota; Tuncel, Aytug; Matsusaka, Hiroaki; Satoh, Ryosuke; Singh, Salvinder; Crofts, Naoko; Hosaka, Yuko; Fujita, Naoko; Hwang, Seon-Kap; Satoh, Hikaru; Okita, Thomas W.
Abstract : Rice lines with enhanced ADPglc synthesis and import into amyloplasts reveal additional barriers within the stroma that restrict maximum carbon flow into starch. Abstract: Previous studies showed that efforts to further elevate starch synthesis in rice ( Oryza sativa ) seeds overproducing ADP-glucose (ADPglc) were prevented by processes downstream of ADPglc synthesis. Here, we identified the major ADPglc transporter by studying the shrunken3 locus of the EM1093 rice line, which harbors a mutation in the BRITTLE1 (BT1) adenylate transporter ( OsBt1 ) gene. Despite containing elevated ADPglc levels (approximately 10-fold) compared with the wild-type, EM1093 grains are small and shriveled due to the reduction in the amounts and size of starch granules. Increases in ADPglc levels in EM1093 were due to their poor uptake of ADP-[ 14 C]glc by amyloplasts. To assess the potential role of BT1 as a rate-determining step in starch biosynthesis, the maize ZmBt1 gene was overexpressed in the wild-type and the GlgC (CS8) transgenic line expressing a bacterial glgC-TM gene. ADPglc transport assays indicated that transgenic lines expressing ZmBT1 alone or combined with GlgC exhibited higher rates of transport (approximately 2-fold), with the GlgC (CS8) and GlgC/ZmBT1 (CS8/AT5) lines showing elevated ADPglc levels in amyloplasts. These increases, however, did not lead to further enhancement in seed weights even when these plant lines were grown under elevated CO2 . Overall, our results indicate that rice lines with enhanced ADPglc synthesis and import into amyloplasts reveal additional barriers within the stroma that restrict maximum carbon flow into starch.